Instrumental and Lyrical Performance in the Components of the Author’s Kurdish Singing - Adil Mohammed Karim; Ehsan Shakr Zalzala; Azad Hama Abdola (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research is entitled (Instrumental and lyrical performance in the components of the author’s Kurdish singing(, a descriptive -analytical research, in which we have studied three basic musical components in two Kurdish songs, the components are (sound, melody, rhythm) for each In the sections of the songs, which we mean (music 1, song 1, music 2, song 2), obviously the researchers have used some methods of analysis of world and oriental music, have developed a special analytical method in the installed. This study is an important starting point for understanding the details of the three main components of Kurdish composed songs, the parts of Kurdish composed songs. The results of this analysis show that there are more differences and sometimes common points in the details of each section. This leads us to the conclusion that Kurdish composed songs are dominated by talent and taste of artistic beauty and knowledge of musical art. Therefore, these songs are multidimensional and rich in several aspects. The paper consists of three main sections, conclusions, and a list of references. The first part, which is the general framework of the research, includes: (Introduction, research problem, research importance, research objectives, limitations, research methods and definition of concepts) do. Section 3: Conducting the research section. At the end of the study, the conclusions, recommendations, suggestions and list of sources are presented. with a summary of the paper in both English and Arabic.